Aplikasi Peringkas Teks Bahasa Indonesia Menggunakan Model Text-to-Text Transfer Transformer (T5) - Yani, Mohammad; Khodijah, Nur Siti; Rendi; Mustamiin, Muhamad (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
In the digital era, information can be easily accessed through various available media such as search engines, academic repositories, social media, news portals, and websites. However, the information available is often presented in lengthy textual form. For instance, information about ’Joko Widodo’ on the Wikipedia page contains at least 8,716 characters of text. Such a long text can be challenging to extract its main points efficiently. Several studies have been conducted on the development of text summarization applications. Nevertheless, a summarization application that accepts input from various formats has not yet been developed. In this research, the author proposes a text summarization system capable of summarizing text using inputs in multiple formats. This text summarization system processes information inputs in the form of text, document files, web pages, and images, which are subsequently summarized using the Text-to-Text Transfer Transformer (T5) model to generate a summarized output that can be stored in various file formats. Evaluation results indicate that text summarization with document or text file inputs yields higher ROUGE scores compared to non-text inputs, reaching an average score of 0.87